Assessement of postmortem intervals using DNA methylation - Pereira, João Leonardo Azevedo Meireles (2020)
Estimation of a corpse’s time of death is an absolute crucial part of many forensic cases. An accurate time placement in a case’s sequence of events is information that can create a suspect list or exempt suspects from it, deeply altering an entire case. Currently, postmortem intervals and time of death is assessed through several physical, metabolic and physiochemical evaluations during autopsy. These evaluations carry strengths, weaknesses and variations, and a more stable and robust procedure would be invaluable to the advancement of forensic sciences. One of the most recent focus for such a possible procedure relies in one of the epigenetic regulations of DNA, the addition of a methyl group to certain cytosines, known as DNA methylation. DNA methylation regulates many aspects of the genome, from silencing tissue specific genes, non-coding sections of DNA, up to tissue specialization and working as a stable long-term response to the environment. This work is a review on procedures, potential biomarkers, possible viability and obstacles in the way of using this regulatory modification of the considerably stable port-mortem DNA